If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + -4) = 6(x + 6) Reorder the terms: -5(-4 + x) = 6(x + 6) (-4 * -5 + x * -5) = 6(x + 6) (20 + -5x) = 6(x + 6) Reorder the terms: 20 + -5x = 6(6 + x) 20 + -5x = (6 * 6 + x * 6) 20 + -5x = (36 + 6x) Solving 20 + -5x = 36 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 20 + -5x + -6x = 36 + 6x + -6x Combine like terms: -5x + -6x = -11x 20 + -11x = 36 + 6x + -6x Combine like terms: 6x + -6x = 0 20 + -11x = 36 + 0 20 + -11x = 36 Add '-20' to each side of the equation. 20 + -20 + -11x = 36 + -20 Combine like terms: 20 + -20 = 0 0 + -11x = 36 + -20 -11x = 36 + -20 Combine like terms: 36 + -20 = 16 -11x = 16 Divide each side by '-11'. x = -1.454545455 Simplifying x = -1.454545455
| p-4=-9+8 | | -1(4)+2= | | 5p+8=13 | | 6x^2-3y=8 | | 1/2(x-9)^2=18 | | 14x+23=5x+266 | | (3x-2)/4=5x-9.9 | | 4(0)+2= | | -6/5y-2/5y=4/5+4/5 | | 5x+11=-27-7x | | (2v+3)(v-1)=0 | | n/2+8 | | 1a-6=6a-4 | | 7x+2(-2x-1+2x)-5x-1=0 | | x+x+x+x+x+x+x+x+x+x+x+x+x=111.3888889 | | 7-10x=27-27x | | 5.3x+2y=14 | | 10-2/3x-5x=-157/3 | | 1/5n-4=-10 | | x+2*3x-1=12 | | 2x+40=12x-8 | | 5/4v=-8 | | u/4-10=26 | | x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x=2005 | | u/4-10 | | z-(-10)=8 | | 40=v/5+12 | | x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x+x=20053 | | x+x=2005 | | 9x+14-8x=-6-11 | | 4(-1)+2= | | 3(2x+5)=3x+4x |